Disulfide Bond Reversible Strategy Enables GSH Responsive‐Transferrin Nanoparticles for Precise Chemotherapy. Issue 10 (30th June 2020) - Luo, Yu; Liu, Xianping; Liang, Kaicheng; Chen, Qian; Liu, Tianzhi; Yin, Bo; Chen, Hangrong
Abstract: Effective delivery of therapeutic agents into brain tissue for therapy of glioma remains a big challenge due to the presence of the blood‐brain barrier (BBB). Herein, a disulfide bond on–off–on triplet regulation strategy is developed to endow transferrin nanoparticles with high up to 18.1% drug‐loading efficiency. Such transferrin nanoparticles of around 70 nm, specifically, DOX@Tfm NPs, are synthesized via self‐assembly of modified transferrin with hydrophobic doxorubicin (DOX), displaying glutathione (GSH)‐responsive DOX release behavior in the tumor microenvironment. These DOX@Tfm NPs maintain the naturally targeted activity of transferrin, which can effectively cross the BBB and target the transferrin receptor overexpressed on the surface of glioma cells for precise chemotherapy of orthotopic glioma. In vivo results confirm that DOX@Tfm NPs can effectively target orthotopic glioma in living mice, achieving enhanced efficiency in inhibiting tumor growth and increasing survival rate without obvious side effects being observed. This study presents a new avenue to develop natural protein materials as promising smart drug delivery systems for clinical transformation. Abstract : A glutathione fast‐responsive transferrin‐drug delivery system based on a novel disulfide bond reversible strategy is developed, which can maintain the naturally targeted activity of transferrin. The obtained self‐assembly transferrin nanoparticles (NPs) have highly efficient drug loading of around 18.1% and readily cross the blood‐brain barrier and effectively target orthotopic glioma in living mice.